2018
DOI: 10.1111/1365-2478.12638
|View full text |Cite
|
Sign up to set email alerts
|

Vertical seismic profiling using a daisy‐chained deployment of fibre‐optic cables in four wells simultaneously – Case study at the Ketzin carbon dioxide storage site

Abstract: The geological storage of carbon dioxide is considered as one of the measures to reduce greenhouse gas emissions and to mitigate global warming. Operators of storage sites are required to demonstrate safe containment and stable behaviour of the storage complex that is achieved by geophysical and geochemical monitoring, combined with reservoir simulations. For site characterization, as well as for imaging the carbon dioxide plume in the reservoir complex and detecting potential leakage, surface and surface‐bore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…This method is based on optical time-domain reflectometry and enables us to register strain changes along optical sensor cables with high spatial and temporal resolution (Parker et al, 2014). Within recent years, a growing number of VSP surveys have been reported, where the DAS method has successfully been applied using sensor cables permanently installed behind casing or along tubing (e.g., Mestayer et al, 2011;Daley et al, 2013;Götz et al, 2018). This deployment method is very convenient as it allows for data acquisition without well intervention.…”
Section: Introductionmentioning
confidence: 99%
“…This method is based on optical time-domain reflectometry and enables us to register strain changes along optical sensor cables with high spatial and temporal resolution (Parker et al, 2014). Within recent years, a growing number of VSP surveys have been reported, where the DAS method has successfully been applied using sensor cables permanently installed behind casing or along tubing (e.g., Mestayer et al, 2011;Daley et al, 2013;Götz et al, 2018). This deployment method is very convenient as it allows for data acquisition without well intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from conventional surface seismic acquisition, the hydrophone arrays, buried geophone, and the fiber optic cables are permanently installed in the vertical seismic profiling systems to achieve long-term monitoring and obtain the geological structure details [152]. This monitoring technology has been successfully used in the Ketzin pilot site and the MRCSP project.…”
Section: Monitoring Technologies In the Assessment Of The Ccs Risksmentioning
confidence: 99%
“…For downhole installations, several studies were performed to evaluate the potential of Vertical Seismic Profiling, by Rector and Mangriotis surveys. Generally, it has been shown that although fiber optic data has a lower signal to noise ratio compared to conventional borehole seismic sensors, the higher spatial resolution allows to acquire high resolution exploration results (e.g., Mestayer et al 2011;Cox et al 2012;Daley et al 2013;Götz et al 2018).…”
Section: Selected Case Studiesmentioning
confidence: 99%